Dawn‐Dusk Asymmetry in Energetic (>20 keV) Particles Adjacent to Saturn's Magnetopause. Issue 2 (9th February 2021) - Liou, Kan; Paranicas, Chris; Vines, Sarah; Kollmann, Peter; Allen, Robert C.; Clark, George B.; Mitchell, Donald G.; Jackman, Caitriona M.; Masters, Adam; Achilleos, Nick; Roussos, Elias; Krupp, Norbert
Abstract: Energetic particles (>∼25 keV) have been observed routinely in the terrestrial magnetosheath, but have not been well studied at the magnetosheaths of the outer planets. Here we analyze energetic electrons and ions (mostly protons) in the vicinity (±1 R S ) of Saturn's magnetopause, using particle data acquired with the low‐energy magnetosphere measurements system, one of the three sensors of the magnetosphere imaging instrument on board the Cassini spacecraft, during a period of ∼14 years (2004–2017). It is found that energetic particles, especially ions, are also common in Saturn's magnetosheath. A clear inward (toward Saturn) gradient in the electron differential flux is identified, suggestive of magnetospheric sources. Such an inward gradient does not appear in some of the ion channels. We conclude that Saturn's magnetopause acts as a porous barrier for energetic electrons and, to a lesser extent, for energetic ions. A dawn‐dusk asymmetry in the gradient of particle flux across the magnetopause is also identified, with a gradual decrease at the dawn and a sharp decrease at the dusk magnetopause. It is also found that magnetic reconnection enhanced flux levels just outside of the magnetopause, with evidence suggesting that these particles are from magnetospheric sources. These findings strongly suggest that Saturn's magnetosphere is most likely the main source of energetic particles in Saturn's magnetosheath and magnetosphere leakage is an important process responsible for the presence of the energetic particles in Saturn's magnetosheath. Key Points: Magnetosphere imaging instrument/low‐energy magnetosphere measurements system low‐energy telescope data are analyzed to study energetic electron and ion fluxes around Saturn's low‐latitude dayside magnetopause Energetic particles are commonly found in Saturn's magnetosheath and their flux levels depend on the energy of particles, local time, and magnetic shear angle The observed dawn‐dusk asymmetry in the energetic particle fluxes is consistent with the magnetic curvature drift and the magnetopause shadowing effect